Impact of Corporate Governance on Sustainability Reporting: A Study of Deposit Money Banks in Nigeria (2012-2021) - Gabriel-Odom, Amarachi Queen; Ikpor, Isaac Monday; Chukwu, Uche (Journal of Accounting Auditing and Business, 2024)
This study examined the impact of corporate governance on sustainability reporting of deposit money banks in Nigeria. Specifically, the study assessed the effect of Audit Committee Activities (ACA), Independent Directors (IND), and Gender Diversity (GDT), respectively, on sustainability reporting of deposit money banks in Nigeria. The dependent variable of the study is Social Sustainability Reporting (SSR), used to proxy sustainability reporting, while corporate governance mechanisms are the independent variables. Ex post facto research design was used with a sample of ten (10) deposit money banks in Nigeria obtained from annual time series data of NSE facts books from 2012 to 2021. Data was analyzed with the use of descriptive statistics. At the same time, a multiple regression model was applied to determine the extent of the effect exerted on sustainability reporting by these corporate governance mechanisms. Findings revealed that audit committee activities have a positive and significant effect on social sustainability reporting, while both independent directors and gender diversity have insignificant effects. The study concluded that corporate governance promotes social sustainability reporting. It was recommended that the shareholders of deposit money banks should appoint experienced independent directors with shareholding interests and include more females on the board as they boost social sustainability reporting.